Current Relevance of Cardiovascular Diseases (Texas Journal of Medical Science, 2022)
Nowadays, cardiovascular diseases are developing very negatively. This disease is very difficult for people nowadays, how long will it take to recover and how much money will it cost to recover. What is the history of the origin of these diseases. About the treatment of the patient and the process used in his treatment.